Climate Games - Andrews, Talbot M.; Delton, Andrew W.; Kline, Reuben (University of Michigan Press, 2025)
Can humanity work together to mitigate the effects of climate change? Climate Games argues we can. This book brings together a decade and a half of experimentation, conducted by researchers around the world, which shows that people can and will work together to prevent disasters like climate change. These experiments, called economic games, put money on the line to create laboratory disasters. Participants must work together by spending a bit of money now to prevent themselves from losing even more money in the future. Will people sacrifice their own money to prevent disaster? Can people make wise decisions? And can people decide wisely on behalf of others? The answer is a resounding yes. Yet real climate change is a complex social dilemma involving the world’s nearly eight billion inhabitants. In the real world, the worst effects of climate change are likely to be felt by developing countries, while most of the decisions will be made by rich, industrialized countries. And while the world as a whole would be better off if all nations reduced their greenhouse gas emissions, any given nation could decide it would be even better off if it continued emitting and let other nations take care of the problem. These disaster experiments test how real people respond to climate change’s unique constellation of challenges and deliver a positive message: People will prevent disaster.